Glycogen storage disease type Ib: role of glucose‐6‐phosphate transporter in cell metabolism and function. Issue 1 (22nd November 2019) - Sim, Sang Wan; Weinstein, David A.; Lee, Young Mok; Jun, Hyun Sik
Abstract : Cellular metabolism generally refers to biochemical processes that produce or consume energy within the cell. Recent studies have established that aberrant metabolic states caused by internal or external stresses and genetic mutations are intertwined with several human pathologies. Gaining insight into these metabolic alterations is, therefore, essential for understanding the pathophysiology of various diseases. Glycogen storage disease type Ib (GSD‐Ib) is an autosomal recessive disorder characterized by hypoglycemia, excessive glycogen accumulation in the liver and kidney, neutropenia, neutrophil dysfunction, and inflammatory bowel disease. GSD‐Ib is caused by a deficiency of glucose‐6‐phosphate transporter (G6PT). Recently, it was reported that deficiency of G6PT also leads to the aberrant proliferation and differentiation of mesenchymal stem cells and impaired regulatory T‐cell function. This review describes the broad impact of altered cellular metabolism resulting from a lack of G6PT activity on cellular function and considers the prospects of developing novel approaches for GSD‐Ib treatment. Abstract :